Oscillatory Asymptotics for the Airy Kernel Determinant on Two Intervals. (26th August 2020) - Blackstone, Elliot; Charlier, Christophe; Lenells, Jonatan
Abstract: We obtain asymptotics for the Airy kernel Fredholm determinant on two intervals. We give explicit formulas for all the terms up to and including the oscillations of order $1$, which are expressed in terms of Jacobi $θ $ -functions.